Analisis Peran Kualitas Audit Terhadap Kinerja Keuangan PT Bank Sentral Asia Tbk - Selfi Putri Lestianingrum; Susan Amelia; Renata Lestari; Fikri Rizki Utama (Indonesia Economic Journal, 2026)
This study aims to analyze the role of audit quality on the financial performance of PT Bank Central Asia Tbk. This research uses a qualitative descriptive approach with a literature study method by collecting data from company financial reports, scientific journals, books, articles, and various references related to audit quality and financial performance in banking companies. The results of the study indicate that audit quality has an important role in maintaining the transparency of financial statements, improving the effectiveness of company supervision, and increasing investor confidence in the company’s financial condition. Audits conducted professionally and independently are able to help companies minimize errors in financial statement recording, detect financial irregularities, and improve the effectiveness of asset and capital management. In addition, audit quality is also influenced by several factors such as auditor independence, auditor competence, compliance with auditing standards, the reputation of Public Accounting Firms, and the company’s internal control system. These factors play an important role in producing objective and reliable audit reports that can support the stability and financial performance of the company. With high-quality audits, companies are able to improve the credibility of financial statements and maintain the stability of company profitability. Therefore, audit quality becomes one of the important factors in supporting the financial performance of banking companies.